PATUNG CAGAR BUDAYA P. W. HOFLAND: SEBUAH TELISIK WARISAN SENI PATUNG EROPA DI KABUPATEN SUBANG - Avianto, Joko Dwi (Jurusan Seni Rupa STSI Bandung, 2013)
According to the current development of artwork in public spaces, sculptures posses a social cultural dimension that cannot be ignored. Attention should be given to restoration and removal of public statues since objects of cultural heritage are related to history and environment. The ever changing social function of space will give impact on the quality of human life. On the other hand, there is a historical dimension that almost never changes. The historical ties refer to the dimension of old spaces within dimension of the current urban spaces. This research focusses on statues that have connection with European art history in Subang Regency as this region was once the Dutch colonial centre for plantation industry in Indonesia. These statues of cultural heritage are known by people in Subang as the statues of Mr Hofland. The Hofland bronze statues are now put in the Museum Wisma Karya Subang as there have been several attemps of stealing them since 1975, and the last attempt was in 2002. Later, these statues were found in damaged condition. Yet, a statue out of three apart from the main statue is still missing.Keywords: Statue, Art, History, Colonial, Plantation________________________________________________________________Berdasarkan perkembangan terakhir karya seni di ruang publik, patung menjadi suatu dimensi sosial budaya yang tidak bisa dikesampingkan. Pemugaran dan pemindahan secara fandal terhadap karya seni patung publik merupakan aktifitas yang patut diperhatikan, mengingat suatu benda cagar budaya memiliki kaitan dengan sejarah dan lingkungannya. Ruang yang terus berubah fungsi sosialnya akan membawa dampak bagi kualitas hidup manusia. Sementara itu terdapat dimensi kesejarahan yang tidak berubah dimana ikatan kesejarahan ini mengacu pada dimensi ruang lama dalam dimensi ruang urban masa sekarang ini. Penelitian ini fokus pada karya patung yang berkaitan dengan sejarah seni di Eropa dan wilayah kabupaten Subang sebagai latar belakang wilayah dimanaterdapat pusat industri perkebunan pemerintah kolonial Belanda. Bagi Kabupaten Subang karya patung ini dikenal sebagai patung tuan Hofland,patung berbahan perunggu ini, kini ditempatkan di museum daerah Wisma Karya Subang. dimana tercatat pada tahun 1975 terjadi percobaan pencurian berulang kali hingga terakhir terjadi percobaan pencurian lainnya di tahun 2002. Kemudian ditemukan dalam keadaan rusak, satu dari tiga buah patung selain patung utamanya masih dinyatakan hilang hingga kini.Kata Kunci: Patung, Seni, Sejarah, Kolonial, Perkebunan